Cognitive and communication interventions : neuroscience applications for speech-language pathologists - Burns, Martha S. (San Diego, CA : Plural Publishing, Inc., 2021)
'Understanding the recent science about how therapy changes the brain can empower clinicians to face the challenges of increasingly demanding medical and educational settings. However, many speech-language pathologists (SLPs) are unaware of the vast impact new neuroscience research has on clinical practice. Cognitive and Communication Interventions: Neuroscience Applications for Speech-Language Pathologists is a practical guide which informs and enables SLP's, clinical psychologists, and other therapeutic professionals to use new research to enhance their clinical outcomes'--
Includes bibliographical references and index.
Keywords: Language Disorders -- therapy; Speech-Language Pathology -- methods; Cognitive Neuroscience -- methods